Comparison between patient control analgesia combine with periarticular drug injection and patient control analgesia alone in total knee arthroplasty - Saari, Fitri; Zakaria@Mohamad, Zamzuri; Sharifudin, Mohd Ariff (2018)
Total knee replacement is the most successful elective arthroplasty operation with good outcome and fewer complication rates. Despite its successful operation, pain after operation period is still the major factor influencing the decision of patient to undergo operation and the outcome of operation. We study the efficacy of periarticular drug cocktail injection in managing postoperative pain in total knee arthroplasty in terms of pain and morphine consumptions.